Head or foot, right or left: analyzing the positions of Isis and Nephthys on coffins and sarcophagi from the Old Kingdom (2663-2160 BC) through Ptolemaic-Roman periods (332BC-395 AD) - Camacho, Kenaya (AUC Knowledge Fountain, 2014)
Isis and Nephthys, two iconic sister goddesses of ancient Egypt are well known for their presence in funerary scenes. In representations of the goddesses as a pair on coffins and sarcophagi dating from the Old Kingdom through the Ptolemaic-Roman Period, there is an alternating dominance between which goddess is placed on the headboard and footboard as well as who is placed on right and left proper of vignettes on these objects. This dissertation will examine what influences the positioning, dominance and orientation of Isis and Nephthys, on coffins and sarcophagi to determine how these positions affect our knowledge of female deities, their alternative positioning in art, and the religious ideals of the divine during a particular time period.